1987
DOI: 10.1017/s0043174500079479
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Mobility of Sulfometuron and Imazapyr in Five Alabama Soils

Abstract: Mobility and sorption of radiolabeled sulfometuron {2-[[[[(4,6-dimethyl-2-pyrimidinyl)amino] carbonyl] amino] sulfonyl] benzoic acid} and imazapyr {(±)-2-[4,5-dihydro-4-methyl-4-(1-methylethyl)-5-oxo-1H-imidazol-2-yl]-3-pyridinecarboxylic acid} were evaluated in five soils representative of the major soil types in Alabama. Thin-layer soil chromatography indicated that sulfometuron was slightly more mobile (average Rf= 0.86) than imazapyr (average Rf= 0.79). Sulfometuron was more subject to sorption (average kd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 23 publications
6
38
0
2
Order By: Relevance
“…Overall, the results are consistent with soil pH having a major influence over the amount of mesotrione adsorbed, accounting for more than half the variations in mesotrione adsorption to soil, by altering the proportions of molecular and anionic forms of mesotrione in soil. Similarly, Mersie and Foy (1985), Shea (1986), and Wehtje et al (1987) attributed the higher adsorption of the sulfonyl urea herbicides at lower pH values to adsorption of the molecular forms.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Overall, the results are consistent with soil pH having a major influence over the amount of mesotrione adsorbed, accounting for more than half the variations in mesotrione adsorption to soil, by altering the proportions of molecular and anionic forms of mesotrione in soil. Similarly, Mersie and Foy (1985), Shea (1986), and Wehtje et al (1987) attributed the higher adsorption of the sulfonyl urea herbicides at lower pH values to adsorption of the molecular forms.…”
Section: Resultsmentioning
confidence: 95%
“…For example, Johnson et al (1995) showed that adsorption of the phenoxy acid 2,4‐D was lower at pH 7 than at pH 5. With the amphoteric compounds, imazaquin and imazethapyr, containing acid and basic functional groups, adsorption decreased as soil pH rose from 3 to 8 (Wehtje et al, 1987; Renner et al, 1988; Stougaard et al, 1990; Loux and Reese, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research results have shown that the potential for cotton rotational injury from imazapic is minimal (Matocha et al 2003;York et al 2000). Variations in soil pH, clay content, and mineralogy have been shown to affect imidazolinone herbicide adsorption and efficacy (Pusino et al 1997;Regitano et al 2000;Stougaard et al 1990;Wehtje et al 1987), which can affect carryover potential to rotational crops (Schroeder 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Morrica et al (2001b) also reported rapid dissipation of imazosulfuron in the field condition. In the sulfonylurea herbicides, greater adsorption at lower pH has mainly been attributed to adsorption of the molecular forms (Mersie and Foy 1986;Shea 1986;Wehtje et al 1987). The pH of the experimental soil was approximately neutral (7.2) which allowed less adsorption of the imazosulfuron to the soil and hence residues were not detected after 90 and 120 days.…”
Section: Residues In the Rice Grains And Strawmentioning
confidence: 99%